Liquidity hoarding and interbank market rates: The role of counterparty risk - Heider, Florian; Hoerova, Marie; Holthausen, Cornelia (Journal of Financial Economics, 2015)
We develop a model of interbank lending and borrowing with counterparty risk. The model has two key ingredients. First, liquidity in the banking sector is endogenous, so there is an opportunity cost of holding liquid assets. Second, banks are privately informed about the risk of their long-term assets, which can lead to adverse selection and high interest rates in the interbank market. We identify a novel form of a market break-down, which can lead to liquidity hoarding. It arises because adverse selection in the interbank market changes the opportunity cost of holding liquidity. We use the model to shed light on developments in interbank markets prior to and during the 2007–09 financial crisis, as well as the effectiveness of policy interventions aimed at restoring interbank market activity.